Circular RNA circDUS2 Is a Potential Biomarker for Intracranial Aneurysm - Chen, Xin; Yang, Shuzhe; Yang, Junhua; Liu, Qingyuan; Li, Maogui; Wu, Jun; Wang, Hao; Wang, Shuo (Frontiers in Aging Neuroscience, 2021)
Backgroud: CircRNAs have been found to play a crucial role in the pathological process of various kinds of diseases.However, role of circRNAs in the formation and rupture of intracranial aneurysm is still unknown. Methods: The differentially expressed circRNAs profiles between superficial temporal arteries (n=5) and intracranial aneurysm (n=5) were analyzed using the Arraystar human circRNAs microarray. Quantitative real-time PCR was used to validate the differential expression of circDUS2. Fluorescence in situ hybridization (FISH) was for the location of circDUS2 in Human brain vascular smooth muscle cell (HBVSMC). Structural analysis was used to speculate the function of circDUS2. Results: 543 upregulated and 397 downregulated significantly in intracranial aneurysm as compared to superficial temporal arteries. Quantitative real-time PCR verified the elevated expression of the upregulated circDUS2. FISH test revealed that the circDUS2 locate in the cytoplasm of brain vascular smooth muscle cells Conclusion: This study showed the differential expression data of circRNAs between STA and intracranial aneurysm, and revealed that circDUS2 is a potential molecular marker for intracranial aneurysm.